Nanotechnologies in food and agriculture - Rai, Mahendra; Ribeiro, Caue; Mattoso, Luiz; Duran, Nelson (Springer International Publishing : Imprint: Springer, 2015)
This book presents a comprehensive overview of new and emerging nanotechnologies. It includes aspects of nanoparticle monitoring, toxicity, and public perception, and covers applications that address both crop growing and treatment of agricultural wastewater. Topics include nanoagrochemicals (nanofertilizers,  -pesticides, -herbicides), nanobiosensors, and nanotechnologies for food processing, packaging, and storage, crop improvement and plant disease control. The group of expert authors is led by an experienced team of editors. .